Broaching the Subjects of Race, Ethnicity, and Culture During the Counseling Process - Day-Vines, Norma L.; Wood, Susannah M.; Grothaus, Tim; Craigen, Laurie; Holman, Angela; Dotson-Blake, Kylie; Douglass, Marcy J. (Journal of counseling and development, 2007)
The authors define broaching as the counselor's ability to consider how sociopolitical factors such as race influence the client's counseling concerns. The counselor must learn to recognize the cultural meaning clients attach to phenomena and to subsequently translate that cultural knowledge into meaningful practice that facilitates client empowerment, strengthens the therapeutic alliance, and enhances counseling outcomes. A continuum of broaching behavior is described, and parallels are drawn between the progression of broaching behavior and the counselor's level of racial identity functioning.